Analiza dyskretnych procesów produkcyjnych oparta na metodzie symulacji komputerowej - Kłos, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The scientific monograph "Analysis of discrete production processes based on the computer simulation method" covers the issues of modeling and simulation of discrete production processes using Tecnomatix Plant Simulation software. The publication proposes a methodology for rapid prototyping of a simulation model of a production system and presents the results of simulation experiments of various models of production systems.
Keywords: modelowanie; symulacja; dyskretne procesy wytwórcze; efektywność systemu produkcyjnego; bufory międzyoperacyjne; modeling; simulation; discrete manufacturing processes; production system efficiency; inter-operation buffers